Challenges and Implementation of Human Rights in the Personality Development of Elderly Prisoners - Tajuddin, Mulyadi Alrianto; Darmawati, Darmawati; Zainuddin, Asriadi; Pramukti, Lilis (Al-Adalah: Jurnal Hukum dan Politik Islam, 2024)
This research aims to analyze the challenges and implementation of human rights in the personality development of elderly prisoners in Merauke Class IIB Prison. The research is limited to two main questions: How is, the personality development of elderly prisoners carriedisÂ  out in the Merauke Class IIB Prison? Secon., what challenges are faced in implementing human rights in providing personality development to elderly prisoners in Merauke Class IIB Prison? This empirical juridical research examines legal regulations based on cases related to the implementation of personality development for elderly prisoners in Merauke Class IIB Prison. The research results show that first, the personality development activities for elderly prisoners carried out by the Merauke Class IIB Prison are limited to spiritual and moral development through direct and familial interaction between facilitators and inmates, systematic and planned development, and individual and group approaches. Second, Merauke Class IIB Prison faced several challenges in implementing human rights for elderly prisoners, such as inadequate provision of facilities and infrastructure, lack of socialization about human rights, which results in officers being less aware of prisoners' rights, and deficiencies in human resource capabilities and skills Necessary to direct organizational goals. Researchers suggest that the implementation of personality development for elderly prisoners must strictly adhere to the Minister of Law and Human Rights Regulation Number 32 of 2018. Every article in it can be taken carefully.